Relationship between flow-mediated vasodilation and cardiovascular risk factors in a large community-based study. Issue 24 (23rd October 2013) - Maruhashi, Tatsuya; Soga, Junko; Fujimura, Noritaka; Idei, Naomi; Mikami, Shinsuke; Iwamoto, Yumiko; Kajikawa, Masato; Matsumoto, Takeshi; Hidaka, Takayuki; Kihara, Yasuki; Chayama, Kazuaki; Noma, Kensuke; et al.
Abstract : Objective: To determine the relationships between flow-mediated vasodilation (FMD) and cardiovascular risk factors, and to evaluate confounding factors for measurement of FMD in a large general population in Japan. Methods: This was a cross-sectional study. A total of 5314 Japanese adults recruited from people who underwent health screening from 1 April 2010 to 31 August 2012 at 3 general hospitals in Japan. Patients' risk factors (age, Body Mass Index, blood pressure, cholesterol parameters, glucose level and HbA1c level) and prevalence of cardiovascular disease (coronary heart disease and cerebrovascular disease) were investigated. Results: Univariate regression analysis revealed that FMD correlated with age (r=−0.27, p<0.001), Body Mass Index (r=−0.14, p<0.001), systolic blood pressure (r=−0.18, p<0.001), diastolic blood pressure (r=−0.13, p<0.001), total cholesterol (r=−0.07, p<0.001), triglycerides (r=−0.10, p<0.001), high-density lipoprotein cholesterol (r=0.06, p<0.001), low-density lipoprotein cholesterol (r=−0.04, p=0.01), glucose level (r=−0.14, p<0.001), HbA1c (r=−0.14, p<0.001), and baseline brachial artery diameter (r=−0.43, p<0.001) as well as Framingham Risk score (r=−0.29, p<0.001). Multivariate analysis revealed that age (t value=−9.17, p<0.001), sex (t value=9.29, p<0.001), Body Mass Index (t value=4.27, p<0.001), systolic blood pressure (t value=−2.86, p=0.004), diabetes mellitus (t value=−4.19, p<0.001), smoking (t value=−2.56, p=0.01), and baseline brachial artery diameter (t value=−29.4, p<0.001) were independent predictors of FMD. Conclusions: FMD may be a marker of the grade of atherosclerosis and may be used as a surrogate marker of cardiovascular outcomes. Age, sex, Body Mass Index, systolic blood pressure, diabetes mellitus, smoking and, particularly, baseline brachial artery diameter are potential confounding factors in the measurement of FMD.